Step length and grade effects on energy absorption and impact attenuation in running - Baggaley, M.; Vernillo, G.; Martinez, A.; Horvais, N.; Giandolini, M.; Millet, G. Y.; Edwards, W. B. (European Journal of Sport Science, 2020)
We sought to examine the effect of step length manipulation on energy absorption and impact attenuation during graded running. Nineteen runners (10F, 9M) ran on an instrumented treadmill at three step lengths (preferred and ±10% preferred) at each of five grades (0°, ±5°, and ±10°) while 3D motion data were captured. Speed was held constant at 3.33 m/s and step length was manipulated by syncing cadence to a metronome. Manipulating step length altered energy absorption (p = 0.002) and impact attenuation (p < 0.0001) across all grades. Energy absorption at the knee joint was most responsive to step length manipulations [Delta range (±10%SL-PrefSL) = 0.076-0.126 J/kg, p < 0.0001], followed by the ankle (Delta range = 0.026-0.100 J/kg, p = 0.001) and hip (Delta range = 0.008-0.018 J/kg, p < 0.006). Shortening step length reduced knee joint energy absorption at all grades with the smallest effect observed during uphill running (Delta = -0.053 J/kg), while large reductions occurred during level (Delta = -0.096 J/kg) and downhill running (Delta = -0.108 J/kg). Increasing step length resulted in greater knee joint energy absorption (p = 0.037) across all grades of running. Impact attenuation was greatest at long step lengths (Delta = 2.708) and lowest at short step lengths (Delta = -2.061), compared to preferred. Overall, Step length influenced the energy absorption and impact attenuation characteristics of the lower extremity during level and graded running. Adopting a shorter step length may be a useful intervention to reduce knee joint loading, particularly during downhill or level running. Elongating step length placed a greater demand on the lower extremity joints, which may expedite the development of neuromuscular fatigue.